Identification of SANCDB compounds against G2019S and I2020T variants of leucine-rich repeat Kinase 2 (LRRK2) for the development of drugs against Parkinson's Disease - Baye, Bertha Cinthia (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2020)
Parkinson's disease is a type of movement disorder that occurs when nerve cells in the brain stop producing dopamine. It is the second neurodegenerative disease affecting 1-2% of people above the ages of 65 years old. There is a worldwide prevalence of 7 to 10 million affected people of all cultures and race. Studies have shown that mutation that causes Parkinson's disease result in increased kinase activity. The c.6055 G > A in exon 41 is the most prevalent LRRK2 variation which causes a substitution of glycine to serine in G2019S in the highly activated loop of its MAP kinase domain. The LRRK2 G2019S variant is the most common genetic determinant of Parkinson's disease identified to date. This work focused on building accurate 3D models of the LRRK2 kinase domain, that were used for large-scale in silico docking against South African natural compounds from the South African Natural Compounds Database (SANCDB; https://sancdb.rubi.ru.ac.za/). Molecular docking was performed to identify compounds that formed interactions with the active site of the protein and had the lowest binding energy scores. Molecular dynamics simulations showed different movements of the protein-ligand complexes and behavioural difference of the wildtype and the variants, all three structures proved to be compact. Network analysis was done to study residue interactions, contact maps, dynamic cross correlations, average BC and average L were used to study the residue interactions and general residue contribution to the functioning of the protein..
Keywords: Antiparkinsonian agents; Parkinson's disease -- Treatment; Protein kinases; Parkinson's disease -- Chemotherapy; Molecules -- Models